On optimal control over quasilinear systems - Trigub, M. V. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We consider the problem of approximately optimal stabilization of quasilinear systems with geometric constraints imposed on control. By using the idea of Krotov global estimates, we justify a method for approximation of the optimal stabilization control and estimate an error in terms of a functional.